Building a bullying-free school culture through the game ‘Detective Bull’ - Aam Imaddudin; Ipah Saripah; Idat Muqoddas (Universitas Pendidikan Indonesia, 2025)
Bullying remains a serious and widespread problem in schools, significantly affecting students' psychological, social, and emotional well-being. To address this issue, a community service program was implemented through the development and introduction of an educational game called Detective Bull at SMAN 2 Lembang, West Bandung Regency. This program aims to increase students' awareness of Bullying roles—such as perpetrators, victims, defenders, and bystanders—and to provide innovative guidance media for school counselors. This initiative was driven by the lack of reflective, engaging, and practical educational tools that naturally reveal students' social dynamics. The program adopted Kolb’s experiential learning model, which consists of four stages: socialization, concrete experience, reflective observation, and abstract conceptualization. A total of 100 students participated in the activity. Results showed students could correctly identify Bullying roles, and demonstrated improved empathy, social sensitivity, and communication. The game also created an active, collaborative, and supportive learning environment. Counselors considered Detective Bull effective as an informal assessment tool. Despite limitations such as time constraints and varying participation levels, this game proved to be a practical and replicable intervention model for school-based community programs. Abstrak Perundungan masih menjadi persoalan serius dan meluas di lingkungan sekolah, yang berdampak besar terhadap kesejahteraan psikologis, sosial, dan emosional peserta didik. Untuk merespons isu tersebut, telah dilaksanakan program pengabdian masyarakat melalui pengembangan dan implementasi media permainan edukatif bernama Detective Bull di SMAN 2 Lembang, Kabupaten Bandung Barat. Program ini bertujuan untuk meningkatkan kesadaran peserta didik terhadap peran-peran dalam perundungan—seperti pelaku, korban, pembela, dan pengamat—serta memberikan alternatif media bimbingan yang inovatif bagi guru BK. Latar belakang kegiatan ini adalah masih minimnya media edukatif yang bersifat reflektif, menyenangkan, dan mudah digunakan untuk mengungkap dinamika sosial peserta didik secara alami. Metode yang digunakan mengacu pada model experiential learning Kolb, melalui empat tahap: sosialisasi, simulasi permainan, refleksi, dan konseptualisasi. Sebanyak 100 peserta didik terlibat dalam kegiatan ini. Hasil menunjukkan bahwa peserta didik mampu mengenali peran dalam perundungan dengan tepat, dan mengalami peningkatan empati, kepekaan sosial, dan komunikasi. Permainan ini juga menciptakan lingkungan belajar yang suportif, aktif, dan kolaboratif. Guru BK menilai permainan ini efektif sebagai alat asesmen informal. Meskipun terdapat keterbatasan waktu dan variasi partisipasi, Detective Bull terbukti sebagai model intervensi yang aplikatif dan dapat direplikasi untuk program pengabdian di sekolah lainnya. Kata Kunci: bimbingan dan konseling; empati; permainan edukatif; perundungan